(3GdCfSGHs - (3GdSeYGfj , YHO GdcQje Hf eMeO Hf efUhQ GdJejej GdSeYGfj GdeQhRj GdTGaYj GdMGaX, CHh SYO,J (B562 (3g` s
(3ChdgG (B:s
(3GdSdGMi HcSQ GdSjf GdegedI hGddGe Cda ai BNQgG GdMGA GdegedI gPg GdfSHI dLeGYI JMedhf GdSdGM s
(3BNQgG (B:s
(3hQhi GdcJGH Yf CHj ehSi GdCfOdSi hef bGd GdYRjRi HGdRGRjjf abO GNWC Je GdeLdO GdNGeS HMeO Gddg s
(3fSNI KGdKIs
(3jHJOF HGdSdGMi hjfJgi HGdYRGRis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B4s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B37 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs